Modulation of Stem Cells as Therapeutics for Severe Mental Disorders and Cognitive Impairments - Zhang, Yongbo; Zhao, Yingying; Song, Xiaopeng; Luo, Hua; Sun, Jinmei; Han, Chunyu; Gu, Xiaohuan; Li, Jun; Cai, Guilan; Zhu, Yanbing; Liu, Zhandong; Wei, Ling; et al. (Frontiers in Psychiatry, 2020)
Severe mental illnesses such as schizophrenia and bipolar disorder can affect 2-4% of the world population. Current medications and diagnostic methods for mental illnesses are not satisfying. In animal studies, stem cell therapy is promising for treating some neuropsychiatric disorders and rescuing cognitive/social deficits not only during development (targeting modulation and balancing) but also following neurodegeneration (cell replacement and regenerating support). We believe that novel interventions such as modulation of specific cell populations combined with stem cell transplantation can improve cognitive and social functions in severe mental illnesses with synaptic/myelin damages. In this review, we have summarized oligodendrogenesis mechanisms and some related calcium signals in neural cells and stem/progenitor cells. The related benefits are discussed from endogenous stem/progenitor cells within the brain and of exogenous stem cells including multipotent mesenchymal-derived stromal cells (MSC), neural stem cells (NSC), pluripotent stem cells (PSC) and differentiated progenitors. These also include mechanisms of oligodendrocyte proliferation, maturation, and myelination for the regenerative effects by both endogenous stem cells and transplanted cells. Among the mechanisms, calcium signaling regulates the GPC/NPC/OPC proliferation, migration and differentiation, dendrite development and synaptic plasticity. By numerous protein annotation and protein-protein interaction databases, a total of 119 calcium-dependent/activated proteins that are related to neuropsychiatry in human are summarized in the investigation. We have also discussed the demyelination pathology of psychiatric symptoms and stem cell treatment effects. As one of the advanced methods, stimulations of stem cells and transplanted cells can take advantages of calcium signaling regulations. Intranasal-to-brain delivery of drug and stem cells with the guidance of brain imaging techniques may provide unique new approach for treating psychiatric disorders. It is expected as well that preconditioning stem cell therapy following precise brain imaging as pathological confirmation is of high potential in translated to the cell clinics. Generally, modulable cells transplantation followed by stimulations should provide paracrine protections, synaptic modulation, and myelin repairs in the brain with severe mental illnesses.